Valeriana pilosa Ruiz & Pav.: a review of traditional uses, phytochemistry and pharmacology - Ascate-Pasos, Manuel Eduardo; Ganoza-Yupanqui, Mayar Luis; Suárez-Rebaza, Luz Angélica; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2020)
Background: The genus Valeriana is native to Asia, but some of its species, such as Valeriana pilosa Ruiz & Pav., they are native to South America and are traditionally used for their sedative or sleeping aid effect. The purpose of the review is to collect the scientific information on V. pilosa regarding its ethnopharmacological uses, chemical composition and biological activities. Methods: 1773 search results were found in the main databases and academic search engines, they were filtered according to access, type of research and relevance; obtaining 70 research documents including scientific articles, books, and theses. Results: V. pilosa is commonly known as ‘’valerian’’ and is traditionally used for its anxiolytic and sedative effect. Valerenic acid is the main compound attributed to its pharmacological activity, although it has only been verified in experimental animals. Also, in Peru, V. pilosa and other species of the genera Valeriana, Astrephia, Plectritis, Betckea and Phyllactis are confused with Valeriana officinalis. Conclusions: Review of V. pilosa ‘‘valerian’’, evidences that it is a plant species used by rural and urban communities; mainly in diseases of the nervous system. However, it is necessary to deepen their phytochemical and pharmacological studies. Keywords: Valeriana pilosa, Valeriana longifolia, Valeriana officinalis, Peru.